Physical and Mathematical Modeling of the Wave Quenching Chamber with the Upper Part in the Form of a Permeable Waterfront - Терещенко. Л. М.; Хомицький, В. В.; Ткаченко, В. О.; Нікітін, I. A.; Харченко, А. Г.; Абрамова, Л. П.; Хижа, I. A.; Кудибин, І. Б. (Київський національний університет імені Тараса Шевченка, 2021)
This paper presents the results of mathematical and physical modeling of the interaction of waves with the wave chamber on cylindrical supports and the upper part in the form of a permeable waterfront. On the basis of the diffraction model the mathematical modeling of refraction and transformation of waves near the structure is carried out. In the presence of a structure, the transformation of waves is co-accompanied by the phenomena of wave destruction at the edges of the structure and the partial reflection of residual waves from the walls of the protective front. Reflection phenomena cause changes in wave heights along the front of the structure. The results of experimental data are given, which showed that the structure with such a construction is resistant to waves, large soil erosion was not observed.

В данной работе представлены результаты математического и физического моделирования взаимодействия волн с волногасящей камерой на цилиндрических опорах и верхней частью в виде проникающей набережной. На основе дифракционной модели проведено математическое моделирование рефракции и трансформации волн у сооружения. При наличии сооружения трансформация волн сопровождается явлениями разрушения волн на краях сооружения и частичным отражением волн от стенок защитного фронта. Явления отражения вызывают изменения высот волн вдоль фронта сооружения. Приведены результаты экспериментальных данных, которые показали, что сооружение при такой конструкции устойчиво к воздействию волн, больших размывов грунта не наблюдалось.

В даній роботі представлені результати математичного та фізичного моделювання взаємодії хвиль із хвилегасною камерою на циліндричних опорах та верхньою частиною у вигляді проникної набережної. На основі дифракційної моделі проведено математичне моделювання рефракції та трансформації хвиль біля споруди. При наявності споруди трансформація хвиль супроводжується явищами руйнування хвиль на краях споруди і частковим відбиттям залишкових хвиль від стінок захисного фронту. Явища відбиття викликають зміни висот хвиль уздовж фронту споруди. Приведено результати експериментальних даних, які показали, що споруда при такій конструкції стійка до дії хвиль, великих розмивів ґрунту не спостерігалось.
Физическое и математическое моделирование волногасящей камеры с верхней частью в виде проникающей набережной
Фізичне та математичне моделювання хвилегасючої камери з верхньою частиною у вигляді проникної набережної
Keywords: wave quenching chamber; physical modeling; coastal protection; permeable waterfront; wave diffraction; хвилегасна камера; фізичне моделювання; захист берегів; проникна набережна; дифракція хвиль; волногасящая камера; физическое моделирование; защита берегов; проницаемая набережная; дифракция волн